Finding Mixture Weibull Distribution - الوكيل علي عبدالحسين (Journal of Economics and Administrative Sciences, 2010)
In this paper a new idea was introduced which is finding a new distribution from other distributions using mixing parameters; wi where 0 < wi < 1 and . Therefore we can get many mixture distributions with a number of parameters. In this paper I introduced the idea of a mixture Weibull distribution which is produced from mixing two Weibull distributions; the first with two parameters, the scale parameter , and the shape parameter, and the second also has the scale parameter , and the shape parameter, in addition to the location parameter, . These two distributions were mixed using a new parameter which is the mixing parameter w which represents the proportion of contribution of each of the component distributions in the new mixture distribution. Different values for the mixing parameter were considered and the probability functions of the mixture Weibull distribution were found. An application of these functions was added using real data and the functions were graphed. The results of the analysis were tabulated in a number of tables that clearly illustrate the idea of the uses of mixture Weibull distribution.